Interventional Pulmonology in the Pediatric Population - Gilbert, Christopher R.; Wang, KoPen; Lee, Hans J. (Seminars in Respiratory and Critical Care Medicine, 2014)
Endoscopic airway interventions within pediatric populations vary considerably. Some of this variance may be related to institutional experience, however, may also be limited by operator experience and available equipment. Previous reports of pediatric bronchoscopic interventional procedures have been identified within the surgical literature; however, newer reports have identified other specialties participating in the care of these patients. Here, we will provide a review of the current relevant medical literature, including an evidence-based review of advanced diagnostic and therapeutic bronchoscopic treatments within the pediatric population.
Keywords: interventional pulmonology; pediatrics; central airway obstruction; endobronchial ultrasound; therapeutic bronchoscopy